Virtual Exhibition of PGMI IAIN Ambon Students Through Technical Assistance and Procedures for Exhibiting Fine Artwork During the Covid-19 Pandemic - Iga Ayu Intan Candra (IAIN AMBON, 2021)
Abstract: The Covid-19 pandemic has interrupted the artistic process that occurs in society. Making people forced to use digital platforms in the process of expression and appreciation of art. During the Covid-19 pandemic, fine arts chose digital media as a way out for the exhibition. This community service is one solution to increase the expression and appreciation of PGMI IAIN Ambon students who will later teach art as classroom teachers. The service activity with the title